Cerebellar Stroke Impairs Executive Functions But Not Theory of Mind - Roca, María (2013)
Even though cerebellar activation has been described during theory of mind (ToM) tasks in neuroimaging studies, no previous studies have investigated ToM in group of patients with cerebellar strokes. In the present study we assessed 11 patients with cerebellar infarction on a variety of executive tests and with the Faux Pas test of ToM. Even if cerebellar patients showed significant deficits on executive tasks relative to a control group, no significant differences were found between the groups on the Faux Pas test. This is the first group study to demonstrate that focal cerebellar lesions don't affect ToM.